2021
DOI: 10.26444/ms/133945
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviours of nursing staff working in a shift system in John Paul II District Hospital in Wadowice

Abstract: Cel pracy. Praca zmianowa jest bardziej szkodliwa dla organizmu niż praca w systemie dziennym-uniemożliwia respektowanie fizjologicznych rytmów okołodobowych człowieka. Aż 70% pracowników pracujących w systemie zmianowym nie jest w stanie określić dokładnego stopnia nietolerancji pracy zmianowej. Celem pracy było poznanie zachowań zdrowotnych pielęgniarek/pielęgniarzy pracujących w systemie zmianowym w zależności od wieku oraz sprawdzenie, czy istnieje zależność pomiędzy oddziałem, na jakim pracuje dana osoba,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
1
5
1
Order By: Relevance
“…Specifically, with age, the “positive mental attitude” has increased, and the work experience has decreased. Similar results were obtained in a study by Waksmaska et al, where statistically significant differences were shown in participants under 40 and over 50 years of age with respect to the level of health behaviors [ 39 ]. In the study by Orszulak et al, it was observed that there was an equally significant correlation between age and total HBI score, revealing a higher prevalence of each type of health behavior among older nursing staff [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, with age, the “positive mental attitude” has increased, and the work experience has decreased. Similar results were obtained in a study by Waksmaska et al, where statistically significant differences were shown in participants under 40 and over 50 years of age with respect to the level of health behaviors [ 39 ]. In the study by Orszulak et al, it was observed that there was an equally significant correlation between age and total HBI score, revealing a higher prevalence of each type of health behavior among older nursing staff [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…A similar result was obtained in a study by Waksma ńska et al, where statistically significant differences were shown in participants under 40 and over 50 years of age regarding the level of health behaviors. The rate of health-promoting behavior undertaken was significantly higher among nursing staff aged 50 years (M = 80.61) compared to participants under 40 years (M = 75.50) [25]. When examining the correlations in a study by Górniak et al, there was a statistically significant relationship between the level of education and the overall health-behavior index.…”
Section: Discussionmentioning
confidence: 94%
“…The prevalence of respondents’ health behaviors was verified using Juczynski’s Health Behavior Inventory (HBI), which consists of 24 questions on personal health-related behaviors [ 6 , 37 ]. The inventory evaluates the prevalence of health behaviors in four categories [ 37 ]: Proper eating habits (PEH); Pro-health activities (PhA); Preventive actions (PA); Positive mental attitude (PMA).…”
Section: Methodsmentioning
confidence: 99%
“…The quality of life as understood here is determined mainly by health status, which, according to the concept of health fields by Marc LaLonde, in over half of cases, depends on lifestyle [ 4 ], viewed as any forms of behavior (actions) manifested by people, which in the light of modern medical knowledge usually cause specific positive (healthy) or negative (unhealthy) effects [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation